2018
DOI: 10.1016/j.ijom.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of bimaxillary surgery in the correction of vertical maxillary excess: retrospective study

Abstract: The aim of this study was to evaluate the precision of bimaxillary surgery performed to correct vertical maxillary excess, when the procedure is sequenced with mandibular surgery first or maxillary surgery first. Thirty-two patients, divided into two groups, were included in this retrospective study. Group 1 comprised patients who received bimaxillary surgery following the classical sequence with repositioning of the maxilla first. Patients in group 2 received bimaxillary surgery, but the mandible was operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Clockwise (CW) rotation is believed to be more accurate using the maxilla-first approach, while counter clockwise (CCW) rotation should be more accurate using the mandible-first approach 4,5 . However, only 3 studies have compared the 2 sequences in large cohort studies, and none have evaluated how CW or CCW rotation influence the clinical outcome when the mandible or maxilla is sequenced first 1,[10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Clockwise (CW) rotation is believed to be more accurate using the maxilla-first approach, while counter clockwise (CCW) rotation should be more accurate using the mandible-first approach 4,5 . However, only 3 studies have compared the 2 sequences in large cohort studies, and none have evaluated how CW or CCW rotation influence the clinical outcome when the mandible or maxilla is sequenced first 1,[10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The latter could vary significantly from patient to patient because EGD may be caused by several etiologies including altered passive eruption (APE), plaque‐/drug‐induced gingival enlargement, anterior dentoalveolar extrusion, vertical maxillary excess, hypermobile upper lip (HUL), short upper lip, and asymmetric upper lip . The treatment modalities indicated comprise a wide range of less or more invasive procedures, including aesthetic crown lengthening, lip repositioning, orthognathic surgery and orthodontics, and other surgical and nonsurgical options – …”
Section: Introductionmentioning
confidence: 99%
“…The latter could vary significantly from patient to patient because EGD may be caused by several etiologies including altered passive eruption (APE), plaque-/drug-induced gingival enlargement, anterior dentoalveolar extrusion, vertical maxillary excess, hypermobile upper lip (HUL), short upper lip, and asymmetric upper lip. [13][14][15] The treatment modalities indicated comprise a wide range of less or more invasive procedures, including aesthetic crown lengthening, 16 lip repositioning, [17][18][19] orthognathic surgery and orthodontics, 15,20,21 and other surgical and nonsurgical options. [13][14][15]22 Information on the prevalence of a few of the different EGD etiologies is available only in special populations; examples include gingival enlargement prevalence among patients receiving various medications, [23][24][25][26] APE prevalence in young adults 27 and in patients who had or had not undergone orthodontic therapy, 28 asymmetric upper lip prevalence among dental students, 29 and vertical maxillary excess prevalence in patients with dentofacial deformities.…”
Section: Introductionmentioning
confidence: 99%
“…Complete BSSO does not require a wide mouth opening, which could cause an alteration of the fixed maxillary position. Salmen et al [ 46 ] and Liebregts et al [ 47 ] reported that in the context of planned maxillary impaction and with most surgical movements, the maxilla-first sequence was more accurate.…”
Section: Surgical Proceduresmentioning
confidence: 99%